الضغوط النفسية وعلاقتها بالعنف المدرسي لدى تلاميذ الرابعة متوسط - بن خليفة، مريم, حامد، مفيد (جامعة الوادي university of Eloued, 2020)
The current of this study aims to identify the relationship between psychological pressure and violence in fourth year Middle as this school year represents fatal year for students .It also aims at showing the individual differences between boys and girls. Through the application of the two measurements of the two researched ; the first is the psychological pressure and school violence if fourth Middle students with other students in the Wadi. The study has reached the following results : -There is a strong bond between the psychological pressure and school violence specially among fourth year Middle. -There also differences of great significance related to violence based on gender. There is a strong bond between the psychological pressure and school violence specially among fourth year Middle school. There also differences of great significance related to violence based on gender
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: الضغوط النفسية، العنف المدرسي; Stress psychologique, violence scolaire; Psychological stress, school violence